2000
DOI: 10.1136/jech.54.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Social inequalities in health related behaviours in Barcelona

Abstract: Objective-This study describes social class inequalities in health related behaviours (tobacco and alcohol consumption, physical activity) among a sample of general population over 14 years old in Barcelona. Design-Cross sectional study (Barcelona Health Interview Survey). Setting-Barcelona city (Spain).Participants-A representative stratified sample of the non-institutionalised population resident in Barcelona was obtained. This study refers to the 4171 respondents aged over 14. Data-Social class was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 36 publications
5
26
0
5
Order By: Relevance
“…Nearly all physical activities examined were practiced more by groups of higher education, agreeing with the findings of other authors 18,30 , except for cycling in both sexes and soccer in men. Soccer was the most played sport by males reaching a prevalence of 20.9%, agreeing well with the study of Séclen-Palacin and Jacoby 18 , who also found higher prevalence of soccer practicing in the lower socioeconomic layer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nearly all physical activities examined were practiced more by groups of higher education, agreeing with the findings of other authors 18,30 , except for cycling in both sexes and soccer in men. Soccer was the most played sport by males reaching a prevalence of 20.9%, agreeing well with the study of Séclen-Palacin and Jacoby 18 , who also found higher prevalence of soccer practicing in the lower socioeconomic layer.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies showed an association between physical activities during leisure time and number of worked hours 18,29 , showing that disadvantaged segments of society would have less time or energy for physical activities during leisure time 30 . Few psychosocial resources and low participation in social groups could also explain the physical inactivity during leisure time in socioeconomically disadvantaged adults 28 .…”
Section: Discussionmentioning
confidence: 99%
“…n 1 : number of studies by educational level; n 2 : number of studies by occupational level. Our findings about a higher consumption of cheese in the higher social class are consistent with previous studies (Popkin et al, 1989;Erkkilä et al, 1999;Borrell et al, 2000). We also observed a positive association between a higher level of education and a greater consumption of milk.…”
Section: Socioeconomic Differences In Food Habits In Europesupporting
confidence: 93%
“…Some reasons may explain this mortality and morbidity inequalities, since lower social groups are exposed to more difficult and risky tasks and do not have such a great interest in their future health. Other important reasons associated with socioeconomic factors are nutrition-related and lifestyle characteristics such as physical activity, alcohol, smoking, and diet (Hulshof et al, 1991;Prätälä et al, 1994;Borrell et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Smoking in southern Europe is more frequent among women in higher educational categories. 6,7,[15][16][17] Our results demonstrate a dynamic process of change in Note. Vertical bars represent 95% confidence intervals.…”
Section: Discussionmentioning
confidence: 94%